Education, Income Distribution and Innovation - Ling Shen (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
In this paper we study the impact of the income distribution on innovation through the demand for quality goods. For simplicity, we assume that there are two types of consumers, rich and poor. The income distribution is measured by the population share of the poor and the relative income of the poor. Contrary to the literature, we assume that both are interdependent through education. The larger the income difference between the poor and the rich, the more individuals undergo education, because individuals can become rich through education. Quality goods are first invented, and then produced by oligopolists. Rich consumers have a higher willingness to pay for the better quality than the poor. Hence, the firms' profit depends on the income distribution of consumers. We focus on the separating equilibrium, where goods of different qualities are sold to different consumers. In this equilibrium, a lower relative income of the poor is good for innovation, and a larger population share of the poor is bad for innovation.
Keywords: O12; O15; D31; D43; O31; I20; 330; inequality; growth; Innovation; Produktqualität; Nachfrage; Einkommensverteilung; Konsumentenverhalten; Bildungsverhalten; Bildungsinvestition; Wirtschaftswachstum; Theorie